Mapping outcomes of liquid marble collisions. Issue 17 (4th April 2019) - Draper, Thomas C.; Fullarton, Claire; Mayne, Richard; Phillips, Neil; Canciani, Giacomo E.; de Lacy Costello, Ben P. J.; Adamatzky, Andrew
Abstract : Collision outcomes between one stationary and another rolling liquid marble can be controlled using Weber number (We * ) and offset ratio. Abstract : Liquid marbles (LMs) have many promising roles in the ongoing development of microfluidics, microreactors, bioreactors, and unconventional computing. In many of these applications, the coalescence of two LMs is either required or actively discouraged, therefore it is important to study liquid marble collisions and establish parameters which enable the desired collision outcome. Recent reports on LM coalescence have focused on either two mobile LMs colliding, or an accelerating LM hitting a sessile LM with a backstop. A further possible scenario is the impact of a mobile LM against a non-supported static LM. This paper investigates such a collision, using high-speed videography for single-frame analysis. Multiple collisions were undertaken whilst varying the modified Weber number (We*) and offset ratios ( X *). Parameter ranges of 1.0 < We* < 1.4 and 0.0 < X * < 0.1, resulted in a coalescence rate of approximately 50%. Whereas, parameter ranges X * > 0.25, and We* < 0.95 or We* > 1.55 resulted in 100% non-coalescence. Additionally, observations of LMs moving above a threshold velocity of 0.6 m s −1 have revealed a new and unusual deformation. Comparisons of the outcome of collisions whilst varying both the LM volume and the powder grain size have also been made, revealing a strong link. The results of this work provide a deeper understanding of LM coalescence, allowing improved control when designing future collision experiments.